APPLICATION OF SQUISHY PLAY THERAPY TO REDUCE PAIN RESULTING FROM INVASIVE PROCEDURES IN PRESCHOOL CHILDREN IN THE WEST ASTER WARD OF DR. SARDJITO GENERAL HOSPITAL, YOGYAKARTA - Afifah Dwi Cahyani; Sumarti Endah Purnamaningsih Maria Margaretha (Jurnal Kesehatan Karya Husada, 2026)
Background: Pain is a very individual subjective experience that can affect adults and children of all ages. Pain can come from disease processes, injuries, procedures and interventions, routine actions are invasive procedures, namely infusion and blood draws. The intravenous therapy procedure causes acute pain for children. According to data from the World Health Organization (WHO), the incidence of infusion in hospitals is quite high, namely 85% per year. Based on survey data of 120 million people out of 190 million patients treated in hospitals using IVs. Purpose : To determine the description of the application of squishy play therapy to reduce pain in preschool children due to invasive procedures. Method : This case study uses a descriptive method, data collection using this method uses interviews and observations. Result : The results obtained after being given squishy play therapy for 3 consecutive days were able to help reduce the pain scale with a decrease in the pain scale value of 2 every day and the mean value was 2. Conclusion : Squishy play therapy can reduce pain due to invasive procedures in preschool children.